Moderators of Treatment for Adolescent Depression. Issue 4 (4th July 2021) - Meyer, Allison E.; Curry, John F.
ABSTRACT: Objective : This brief report reviews the literature on moderators of treatment for adolescent depression. Treatment moderators can help to guide the process of personalizing intervention to individual patient characteristics. Method : We conducted a systematic search in PsycInfo and PubMed. We also reviewed references of previous reviews and searched for moderator analyses conducted secondary to published efficacy studies. Results : We review 27 studies that address the following categories of moderators: demographics, severity indices, comorbidity, contextual factors, history of abuse or trauma, and cognition and coping. We found limited evidence that demographic, contextual, or cognitive variables consistently moderated treatment for adolescent depression. There was some indication of moderation by race/ethnicity, presence of some comorbid disorders, greater depression severity, and a history of trauma. Conclusion : Our review found inconsistent findings across studies, likely due to the strong impact of predictors relative to moderators and limited statistical power. More research using innovative statistical approaches is necessary before treatment tailoring can be an empirically-based process.